2021
DOI: 10.1111/bioe.12878
|View full text |Cite
|
Sign up to set email alerts
|

He Jiankui´s gene‐editing experiment and the non‐identity problem

Abstract: Although genetic engineering cannot be considered a new technology, CRISPR has taken it to a whole new level. The quickness and precision of this new biotechnology, as well as its wide range of applications, make CRISPR nothing less than a revolution. 1 The history is by now well known: the work of F. Mojica on the immune system of archaea and bacteria in the 1990s served as the basis of the development by J. Doudna and E. Charpentier in 2012, and shortly after by F. Zhang, of a gene-editing technology that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…(2021) [25] Analyze To analyze all the ethical arguments against genomic editing and point out their merits and flaws.…”
Section: Alonso and Savulescumentioning
confidence: 99%
See 4 more Smart Citations
“…(2021) [25] Analyze To analyze all the ethical arguments against genomic editing and point out their merits and flaws.…”
Section: Alonso and Savulescumentioning
confidence: 99%
“…Petre discussed using the future generations’ perspective that genetic modification may lead to the uniformization of genes involved in reproductive recombination, leading to health risks [ 10 ]. Alonso and Savulescu analyzed He Jiankui’Ys gene-editing experiment on the Chinese twins and the ethical dilemma surrounding the experiment by discussing the non-identity problem [ 25 ]. Li and Zhang analyzed the ethics of embryo gene designing (EGD) by using the Confucianism approach and concluded that this approach allows therapeutic EGD with risks including prejudice, playing God/nature, and commodifying [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations